Verification of Meaning in Za'ba's Philosophy - Nordin, Munif Zarirruddin Fikri (Melayu: Jurnal Antarabangsa Dunia Melayu, 2024)
Verification of meaning is the main principle in evaluating the content of expression, whether its meaning is accepted or rejected. In Arab-Islamic and Western philosophies, this principle has been critically studied, especially since the beginning of linguistic shift in the early 20th century. In Malay philosophy, although the verification of meaning is not pursued as in Arab-Islamic and Western philosophies, the awareness of its importance, especially in the concept of original meaning and special meaning as well as the basic method of differentiating meaning has been shown by Za‘ba. This article aims to (1) explain the concept of verification of meaning in Za‘ba’s philosophy, and (2) elaborate on the method of verification of meaning in his philosophy. The data on the concept of verification of meaning involve Za‘ba’s (1919, 1980, 2009) thoughts in the poem titled Kejatuhan Kaum Islam, and the concept of right and wrong in Falsafah Takdir and Perangai Bergantung pada Diri Sendiri. The data on the method of verification of meaning are sourced from Za‘ba’s (2000, 2002) thoughts on deficiency of meaning in Pelita Bahasa Melayu Penggal I-III and differences in meaning in Ilmu Mengarang Melayu. Through the discussion, it was found that awareness and philosophical responsibility were implemented by Za‘ba in laying the foundation for the formation of verification of meaning through the concepts of true, false, meaningful and meaningless, in addition to presenting the conceptual proposal regarding the verification of meaning. He also introduced the method of verification of meaning through the principles of conforming to reality and cognitive reasoning. Full text : PDF